1991
DOI: 10.1002/art.1780340209
|View full text |Cite
|
Sign up to set email alerts
|

Clinical correlations with serum C1q levels in patients with rheumatoid arthritis

Abstract: Previous studies have suggested that serum Clq levels measured during the first 5 years of rheumatoid arthritis (RA) may be predictive of the extent of subsequent joint damage. To further evaluate the clinical significance of this marker in RA, levels of Clq were measured by radial immunodiffusion in serum samples from 107 well-characterized patients with RA. Mean levels of Clq were higher in patients with a disease duration 5 5 years (173 pg/ml) than in patients with a disease duration >5 years (148 pglml) (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…C3b was also present on the cartilage surface of RA patients; thus, this study clearly showed that C1s can activate the downstream complement cascade thereby causing irreversible damage. It has also been shown that the level of C1q in serum correlates with clinical disease activity (CDA) in RA patients ( 144 146 ). In mouse model of RA, C3b gets deposited first on the surface of cartilage vs. synovium and increased rapidly from 4 to 120 h (Figure 2 ).…”
Section: Initiation Of Rheumatoid Arthritismentioning
confidence: 99%
“…C3b was also present on the cartilage surface of RA patients; thus, this study clearly showed that C1s can activate the downstream complement cascade thereby causing irreversible damage. It has also been shown that the level of C1q in serum correlates with clinical disease activity (CDA) in RA patients ( 144 146 ). In mouse model of RA, C3b gets deposited first on the surface of cartilage vs. synovium and increased rapidly from 4 to 120 h (Figure 2 ).…”
Section: Initiation Of Rheumatoid Arthritismentioning
confidence: 99%
“…From the viewpoint of sensitivity, blood levels of C1q can be quantified, demonstrating its suitability for minimally invasive blood tests. However, from the viewpoint of specificity, blood levels of C1q are increased in rheumatoid arthritis [ 21 ] and sarcopenia [ 22 ]. Furthermore, considering that CKD is a consequence of numerous and diverse primary diseases with complicated underlying pathology, it will be difficult to diagnose CKD solely on the basis of blood levels of C1q.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that the consumption of serum C3 was reduced in CIA mice treated with anti-CII Fabs, which lacks the Fc portion as the binding site of complements; furthermore, the in vitro complement inhibition assay showed that ICs-mediated activation of C3 complement was suppressed by anti-CII Fabs. It has been reported that the provoked level of C3a in the serum of RA patients is correlated with laboratory and clinical manifestations of RA [4,26], whereas the reduced levels of C3 are comparable to those of healthy subjects [27]. The activated protein of C3a is a potent mediator involved in inflammatory responses, including alteration of vascular permeability, opsonization for inflammatory leukocytes and activation of release pro-inflammatory cytokines [28]; moreover, murine CIA suppressed by the C3 convertase inhibitor has been reported [29].…”
Section: Discussionmentioning
confidence: 99%